Close Relationship between cIAP2 and Human ARDS Induced by Severe H7N9 Infection. (7th April 2019) - Qin, Chu; Sai, Xiao-yan; Qian, Xiu-fen; Wu, Yan; Zou, Li-fei; Wang, Hong-mei; Bian, Tao; Yan, Zheng
Abstract : Background . cIAP2 is involved in necroptosis as a key upstream regulation factor. We aimed to investigate the role of cIAP2 in ARDS/ALI induced by H7N9 virus through regulating the RIPK1/3 necroptosis pathway. Methods . Lung tissues of 11 patients who died from ARDS-complicated H7N9 infection between 2013 and 2016 were obtained as the H7N9-ARDS group. Lung tissues near benign lung nodules were acquired as the control group. Histological changes were evaluated by H&E staining. Protein levels of cIAP2, RIPK1, RIPK3, p-RIPK3, MLKL, and p-MLKL in the lung tissues were detected by Western Blot. The mRNA levels of cIAP2, RIPK1, and RIPK3 were detected by real-time PCR. Results . H7N9 virus infection had a high mortality, with ARDS being the leading cause of death. The protein level of cIAP2 in the experimental group was lower than that in the control group (P<0.05). However, the experimental group showed higher RIPK1, RIPK3, and p-RIPK3 protein levels than the control group (P<0.05), as well as the expression level of MLKL and p-MLKL protein, which is a key downstream protein in necroptosis (P<0.05). Conclusion . In tissues from patients with fatal H7N9, downregulation of cIAP2 and induction of necroptosis was observed. We could speculate that necroptosis of the pulmonary epithelium is associated with severe H7N9 infection leading to ARDS. Thus, necroptosis inhibition may be a novel therapy for H7N9 influenza virus.